It's Complicated—Adolescent Grief in the Time of Covid-19 - Weinstock, Louis; Dunda, Dunja; Harrington, Hannah; Nelson, Hannah (Frontiers in Psychiatry, 2021)
There is a real possibility of a second pandemic, a grief pandemic. There are estimated to be over 1 million children and young people bereaved because of Covid-19. Adolescent grief is unique because of bio-psycho-social factors such as increased risk-taking, identity-formation, and limited capacity for emotional regulation. In this article, we will argue that adolescents are at increased risk of developing complicated grief during this pandemic, and that it is vital that services are improved to recognize and address this need before the grief turns into secondary problems like anxiety, depression, substance abuse. Complicated grief in adolescents is widely underrecognized and often misdiagnosed as mental health problems, addictions, and offending behavior. For example, 25% of under 20s who take their own life have experienced childhood bereavement and 41% of youth offenders have experienced childhood bereavement, compared to only 4% of the general population. Many of the broader risk factors for complicated grief were already on the rise before this pandemic, including increased reports of loneliness amongst young people, and the collapse of collective structures to help us through grief. We propose that this pandemic can be a catalyst for mental health professionals to support and nurture the caring communities emerging in this time as an essential resource that will prevent the grief pandemic.